The Level of Knowledge of the Community About Heart Health in The Covid-19 Pandemic Era - Harris Hasan; Raynaldo, Abdul Halim (TALENTA Publisher, Universitas Sumatera Utara, 2022)
Background: Cardiovascular disease is still a global health problem. Data obtained from the World Health Organization (WHO) states that the death rate from cardiovascular disease (CVD) is 17.7 million people every year and 31% is the cause of all global deaths. The purpose of this study was to determine the level of public knowledge about heart health in the covid-19 pandemic era. Method: The sampling technique used consecutive sampling, namely subjects who came and met the inclusion criteria were included in the study until the number of samples was met. This study is expected to provide information to the public about heart health and its relationship to the era of the covid-19 pandemic in the community/employees in the USU Medical Faculty Results: In this study, the number of samples was 100 people, the age group > 30 years (62%), while the age group ≤ 30 years (38%). The majority of the sample works as official governments 40 people (40%), had good score predicate, good level of knowledge is Government Employees 20 peoples (20%), health workers (20%), while the level of education is Strata 1. Conclusion: The level of knowledge of the community about heart health in the Covid-19 pandemic era is good with education level Strata 1 and most of them are Government Employees